Caffeine addiction and determinants of caffeine consumption among health care providers: a descriptive national study - Amer, S A; AlAmri, F A; AlRadini, F A; Alenezi, M A; Shah, J; Fagehy, A A; Shajeri, G M; Abdullah, D M; Zaitoun, N A; Elsayed, M (European review for medical and pharmacological sciences, 2023)
Caffeine is the most commonly used psychostimulant compound with a long history of worldwide consumption. Consuming low to moderate doses of caffeine is generally safe and quite beneficial; however, several clinical studies show that high doses could be toxic.  Additionally, caffeine users can become dependent on the drug and find themselves unable to reduce consumption despite impending and recurrent health problems associated with continued use. This study was conducted to explore the prevalence, determinants, and positive and negative effects of caffeine consumption among governmental health care providers (HCPs) who were caffeine users. It aims to determine the frequency of caffeine dependence and addiction in the Kingdom of Saudi Arabia (KSA) in January 2020. This cross-sectional study recruited 600 randomly selected HCPs from all regions of KSA, who fulfilled the selection criteria through a self-administrated, online-validated questionnaire composed of three main parts using the DSM-IV to diagnose dependence and probable addiction. The majority of the studied HCPs were females (67.8%), nonsmokers (82.0%), and Saudis (80.5%), with a mean age of 35 years. According to the DSM-IV, the prevalence of caffeine consumption was 94.3%. Caffeine dependence was reported in 270 (47.7%), while 345 (60.9%) were diagnosed as addicts. The most commonly consumed caffeine-containing substances were coffee and its variants/types (70%), tea (59%), and chocolate (52%), with each person spending about 220 SR per week on them. The main reported adverse effects, in descending order, were sleep disturbances, stomach problems, and cardiac symptoms. The most positive effects reported of caffeine consumption were feeling active, alert, confident, and happy. These findings were significantly affected by sex, occupation, and general health. Caffeine use, dependence, and addiction are common among government HCPs in KSA. Caffeine has both positive and negative effects on this population and further research is necessary to better understand the long-term consequences of caffeine consumption.